Women's experience of a myocardial infarction: 5 years later. - Sjöström-Strand, Annica; Ivarsson, Bodil; Sjöberg, Trygve (Scandinavian Journal of Caring Sciences, 2011)
Scand J Caring Sci; 2010 Women's experience of a myocardial infarction: 5 years later Background: Myocardial infarction (MI) has long been seen as a male disease despite the fact that it is also a health problem for women. Factors that may influence their recovery, such as co-morbidity and requirements for support, have received less scientific attention. Aim: To explore and describe how women conceived their health and daily life 5 years after an MI. Method: An explorative and descriptive approach inspired by phenomenography was chosen as the design. The present study includes 12 women who have been described in earlier short-term studies. Findings: The women described how the MI caused limitations in their lives even 5 years after the MI. They experienced physical restrictions, fatigue and also other health complaints. Furthermore, the older women suffered from various co-morbidities such as diabetes, kidney disease, high blood pressure, and stroke. Some women did not perceive their heart disease to interfere in daily life. Many of the women had thoughts about having a new MI. Furthermore, some women were grateful and described it as having a second opportunity. Conclusion: The present study indicates how women in the recovery process 5 years after an MI still need support to continue with lifestyle changes. The women continue to struggle with different kinds of issues, such as financial stress, co-morbidity and side effects of medication. Support from the health care only in the first year after the MI is not enough. The women should benefit from the possibility to visit or consult professionals in primary care with knowledge of CHD.
The information about affiliations in this record was updated in December 2015. The record was previously connected to the following departments: Thoracic Surgery (013230027), Division of Nursing (Closed 2012) (013065000)